THE EFFECT OF FEAR PERCEPTIONS ON CIGARETTE PACK IMAGE MESSAGES ON THE INTENTION TO STOP SMOKING STUDENTS FACULTY OF SHARIA AND LAW - Sarah Fadhila Siregar; Putra Apriadi Siregar; Azhari Akmal Tarigan (International Archives of Medical Sciences and Public Health, 2021)
Introduction: The policy for picture messages on cigarette packs isregulated in the Minister of Health Regulation No. 57 of 2017concerning Renewal of Inclusion of Warnings and HealthInformation on Tobacco Product Packaging. The purpose ofembedding Pictorial Health Warnings (PHW) on cigarette packs is tocreate fear and motivate someone to quit smoking. Method: Thisstudy uses a quantitative research approach with a cross-sectionaldesign using primary data. This research was conducted at theFaculty of Sharia and Law UIN North Sumatra. From May to July2021. The population in this study was 2.469 students. The samplingtechnique used was purposive sampling. The sample of this studywere 318 teenagers. Data analysis using descriptive analysis andcorrelation test using SPSS 22. Result: There is an influence betweenthe perception of fear in the picture message smoking causes oralcancer (p-value <0.001 r = 0.373), picture message smoking causeslung cancer (p-value <0.001 r = 0.260), picture message smokingcauses throat cancer (p-value <0.001 r = 0.425), smoking picturemessages caused lung and laryngeal cancer (p-value <0.001 r =0.420) and smoking picture messages caused throat cancer (p-value<0.001 r = 0.272) on intention to quit smoking students of the Facultyof Sharia and Law UIN North Sumatra. Conclusion: The more afraidsomeone sees the picture message on the pack of cigarettes, thehigher the intention to quit smoking. It is hoped that the governmentcan expand the picture message on cigarette packs to increase thedesire to quit smoking and reduce the number of smokers inIndonesia.